Sodium Salicylate as Feed Additive in Broilers: Absence of Toxicopathological Findings - Mayra Carraro Di Gregorio; Elaine Renata Motta de Almeida; Claudia Momo; Cristiane Soares da Silva Araújo; Isis Machado Hueza; Newton Andréo-Filho; Leonila Ester Reinert Raspantini; André Tadeu Gotardo; Silvana Lima Górniak (Animals, 2023)
Antimicrobial growth promoters (AGPs) in animal production have been related to the increase in multidrug-resistant bacteria. The AGP ban in many countries has highlighted the growing need for alternatives for feed additives. Considering the non-antibiotic anti-inflammatory theory of AGPs, chicks received three different doses of sodium salicylate (SS) in feed (10, 30, 90 mg/kg), basal diet (BD) was used as a negative control, and zinc bacitracin (ZB) was used as a positive control. Chicks were individually housed to increase the accuracy of the dose of SS ingested. Performance parameters and footpad dermatitis were evaluated weekly, while haematology, serum biochemistry, histopathology, and tibial dyschondroplasia were determined on Days 21 and 42. A linear dose-dependent decrease in haemoglobin concentration was observed, but the values were within the normal reference range. Among all the other evaluated parameters, no relevant differences between treatments were observed; however, not even the AGP group performed better than the control group. It is possible that the conditions in which the birds were raised were not stressful enough to allow for anti-inflammatories to demonstrate their beneficial effects on performance. Studies should be conducted where the animals are exposed to commercial conditions, as the presence of natural stressors could allow a better evaluation of the efficacy of the anti-inflammatory agent as a growth promoter.